The Codification of Jewish Law and an Introduction to the Jurisprudence of the "Mishna Berura" - Broyde, Michael J. (Academic Studies Press, 2014)
The Mishna Berura is, without a doubt, Rabbi Israel Meir Kagan's greatest and most complex contribution to the canon of Orthodox Jewish Law; it is a singular work that synthesizes Jewish traditions, laws, and mores into a practical halakhic guide to daily religious life. For all of his traditionalism, Rabbi Kagan was an iconoclast, and the Mishna Berura broke from many of the traditional approaches of deciding halakhic directives. Instead, he favored studying, engaging, and asserting decisions in a nuanced, almost natural approach to how ethical people should live their daily lives consistent with Jewish law. Today, the Mishna Berura has gained widespread recognition and is considered authoritative by essentially all of contemporary Orthodox Jewry, a measure of greatness that few works of Halakha have attained. Michael J. Broyde and Ira Bedzow here investigate this seminal text and explore its background and decision-making process.